2014
DOI: 10.1007/s11999-014-3900-7
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha Defensin-1 Biomarker Assay can be Used to Evaluate the Potentially Infected Total Joint Arthroplasty

Abstract: Background Diagnosing a periprosthetic joint infection (PJI) requires a complex approach using various laboratory and clinical criteria. A novel approach to diagnosing these infections uses synovial fluid biomarkers. Alpha defensin-1 (AD-1) is one such synovial-fluid biomarker. However little is known about the performance of the AD-1 assay in the diagnosis of PJI. Questions/purposes We sought to (1) determine the sensitivity and specificity of the AD-1 assay in a population of patients being evaluated for PJI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
118
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 10 publications
5
118
1
3
Order By: Relevance
“…Techniques to enhance the sensitivity of intraoperative cultures such as sonication cultures of explanted components were not routinely performed in our institution, possibly overestimating culture-negative PJIs. Lastly, recent studies from the last 2 years have shown that both synovial fluid CRP and a-defensin are highly accurate markers of PJI [1,5,6]; however, neither was included in this study. The reason for this was the lack of supportive data for either of those markers at the time this study was conceptualized in 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques to enhance the sensitivity of intraoperative cultures such as sonication cultures of explanted components were not routinely performed in our institution, possibly overestimating culture-negative PJIs. Lastly, recent studies from the last 2 years have shown that both synovial fluid CRP and a-defensin are highly accurate markers of PJI [1,5,6]; however, neither was included in this study. The reason for this was the lack of supportive data for either of those markers at the time this study was conceptualized in 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The four synovial fluid biomarkers with the highest patient numbers evaluated for this purpose were CRP [5,6,13,15,16,18,20,21], IL-6 [4,6,[9][10][11][12]19], adefensin [1,5,6], and IL-1b [4,6,9,12], respectively. Although a-defensin clearly shows the highest diagnostic accuracy, it has only been evaluated in three studies to the date of our review, two of which emanate from the same group of researchers.…”
Section: Discussionmentioning
confidence: 99%
“…MSIS = Musculoskeletal Infection Society, PJI = periprosthetic joint infection, ESR = erythrocyte sedimentation rate, CRP = C-reactive protein, and WBC = white blood cell, and HPF = high-power field. Sensitivity and specificity of alpha-defensin in the diagnosis of PJI, according to Deirmengian et al 17 , Deirmengian et al 27 , Bingham et al 26 , and…”
mentioning
confidence: 99%
“…here were 10 articles reporting 11 evaluations 13,14,17,18,[26][27][28][29][30][31] that contributed to our estimates of diagnostic accuracy for both tests. Six studies explored the diagnostic accuracy of alpha-defensin for PJI 13,17,[26][27][28]31 , while the remaining 5 studies explored the diagnostic accuracy of leukocyte esterase for PJI 14,17,18,29,30 .…”
mentioning
confidence: 99%
“…In 2014, Deirmengian et al [3] published the evolving use of biomarkers for the investigation of patients with potential PJI. Synovial alpha defensin 1 is one such biomarker that shows accurate results, with nearly 100% sensitivity and specificity [1,2,4].…”
mentioning
confidence: 99%